2013
DOI: 10.1152/jn.00239.2012
|View full text |Cite
|
Sign up to set email alerts
|

Updating of the spatial reference frame of head direction cells in response to locomotion in the vertical plane

Abstract: Many species navigate in three dimensions and are required to maintain accurate orientation while moving in an Earth vertical plane. Here we explored how head direction (HD) cells in the rat anterodorsal thalamus responded when rats locomoted along a 360° spiral track that was positioned vertically within the room at the N, S, E, or W location. Animals were introduced into the vertical plane either through passive placement (experiment 1) or by allowing them to run up a 45° ramp from the floor to the verticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 32 publications
(41 reference statements)
3
36
0
Order By: Relevance
“…Returning to how HD cells fired when the rat is locomoting on a vertical wall, Stackman et al (2000) showed that HD cell tuning curves were identical to those seen when rats locomoted on the floor. Similar findings were also reported both when rats traversed a square-shaped ring that was positioned vertically (Calton & Taube, 2005), and when rats traversed a spiral track that was positioned vertically (Taube et al, 2012). …”
Section: ) What Reference Frame Were the Animals Using In The Verticsupporting
confidence: 78%
See 1 more Smart Citation
“…Returning to how HD cells fired when the rat is locomoting on a vertical wall, Stackman et al (2000) showed that HD cell tuning curves were identical to those seen when rats locomoted on the floor. Similar findings were also reported both when rats traversed a square-shaped ring that was positioned vertically (Calton & Taube, 2005), and when rats traversed a spiral track that was positioned vertically (Taube et al, 2012). …”
Section: ) What Reference Frame Were the Animals Using In The Verticsupporting
confidence: 78%
“…Thus, both models can account for how a HD cell fires when an animal locomotes in a vertical plane. The two models can be distinguished by monitoring cell firing when the animal traverses a ceiling in an inverted position (Calton & Taube, 2005) and from studies when an animal actively locomotes, or is passively placed, into the vertical plane (Taube et al, 2012). The former study supports an Earth-based reference frame, while the latter study supports a reference frame based on the animal's plane of locomotion.…”
Section: Figurementioning
confidence: 99%
“…The lack of vertical direction information in the thalamus resembles the early finding of HD cells in the lateral mammillary nuclei, which were insensitive to the vertical head tilt of rats (Stackman & Taube, ), although we should be mindful of the difference in structures (thalamus versus mammillary nuclei) and environments (3D spaceship versus 2D plane), and the limitations of the recording apparatus used in this early rat study. The vertical insensitivity of the thalamus might also be related to previous findings that showed HD cells in the rat ATN maintained the preferred direction on the vertical wall as if the wall was an extension of the floor, and the HD cells only cared about the rotation along the body axis, not the rotation of the body axis relative to the vertical gravity axis (Calton & Taube, ; Taube et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…The absence of cells tuned to an intermediate angle, and limitations in the apparatus which could not unambiguously detect pitch angles smaller than 40°, made it difficult to provide clear evidence of vertical direction encoding. In several other studies, HD cells were recorded when rats were climbing a vertical plane or were on a ceiling (Calton & Taube, ; Taube, Stackman, Calton, & Oman, ; Taube, Wang, Kim, & Frohardt, ). The results indicated that HD cells responded to an animal's direction relative to the local plane of locomotion, as if the new vertical plane was an extension of the horizontal floor.…”
Section: Introductionmentioning
confidence: 99%
“…Bats have been shown to differ from rodents in the activity of specific brain regions and circuits. Studies of place, head‐direction, and grid cells in navigational behavior have shown clear coding of three dimensions in bats (Yartsev and Ulanovsky, ), but only variations of two‐dimensional coding in rodents (Stackman et al, ; Hayman et al, , ; Taube and Shinder, ; Taube et al, ; Jeffery et al, ). These findings demonstrate functional differences between theses species and reinforce the idea that the two‐dimensional existence of rodents and the three‐dimensional existence of bats are different.…”
mentioning
confidence: 99%